Filled with spirit and power : Protestant clergy in politics - Olson, Laura R., 1967- (State University of New York Press, 2000)
"In Filled with Spirit and Power, Laura R. Olson explores the variety of orientations urban Protestant clergy display regarding political involvement, as well as the many factors that shape their activity. In the typical urban setting of Milwaukee, Wisconsin, the choices pastors make about political involvement are shaped in a profound way not only by their specific religious traditions, but also by the socioeconomic status of the neighborhoods in which they serve. Pastors who serve in economically disadvantaged central city neighborhoods spend the most time on politics, because they come into contact with poverty and its consequences on a daily basis."--Jacket.